Strategi Madrasah dalam Pembinaan Prestasi Peserta Didik - Muffidah, Faridatul; Rohmah, Nafilatur (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
Students at MI Tarbiyatus Sa’adah have achieved many accomplishments, both academically and non-academically. These achievements can be achieved because of MI Tarbiyatus Sa’adah’s effective strategies, which include creating development programs that support student achievement. This research aims to: (1) Describe the student achievement development programs at MI Tarbiyatus Sa’adah, (2) Describe the supporting factors for student achievement development at MI Tarbiyatus Sa’adah, (3) Describe the inhibiting factors for student achievement development at MI Tarbiyatus Sa’adah. This study uses a qualitative descriptive method. Data collection is done through interviews, observations, and documentation. Data validity is checked using source and technique triangulation. The results show that: 1. MI Tarbiyatus Sa’adah has a strategy for improving student achievement consisting of 7 stages: planning (identification), resource preparation, socialization, program implementation, appreciation, evaluation, and development. 2. Supporting factors for student achievement development include internal factors such as student character, interests, and talents, and external factors such as a safe and comfortable school environment, the role of the head of madrasah, funding allocation, teacher loyalty and commitment, and facilities. 3. Inhibiting factors include the multifunctionality of facilities and a tight schedule of development activities. To address these challenges, the madrasah collaborates with external parties regarding facility limitations and adjusts schedules to align with the availability of practice spaces and mentors.